Upaya Hukum Pasien Terhadap Tindakan Medis Yang Didasarkan Pada Persetujuan Medis - Binsar Parulian Sitanggang; Bismar Nasution; Muhammad Ekaputra; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. Approval of medical treatment carried out by the patient or the immediate family of the patient with the doctor can be held accountable in a civil or criminal manner. Therefore, it is necessary to examine the civil liability of medical personnel for medical treatment based on the approval of medical measures. criminal liability of medical personnel for medical action based on approval of medical action and patient's legal remedies for losses resulting from medical actions based on approval of medical action.   Keywords: doctor, patient and medical action approval